Analysis of the physical properties of a boron meter based on He-3 neutron detector - Qi-Dong Dai; Guo-En Fu; Can-Hui Wang; Xun-Cheng Zong; Hong-Bo Wang; Can Cui (Alexandria Engineering Journal)
Boron meter is commonly used for real-time monitoring of boron concentration in the primary circuit water of pressurized water reactors to ensure the safe operation of the reactor. This paper introduces the use of Am-Be neutron source and He-3 neutron detector for a boron meter. It analyzes the physical properties of a boron meter, including the energy spectrum characteristics of Am-Be neutron sources, the sensitivity of He-3 neutron detector, radiation shielding of the boron meter’s detection device, and the fitting relationship between neutron count rate and boron concentration. The boron meter was accurately physically modeled using the MCNP program, and the calculated results were comprehensively compared with experimental results. A method using correction factor μ to adjust the count rate’s calculated results was proposed. The research results show that the sensitivity of He-3 neutron detectors, the dose rate on the surface of the boron meter detection device, neutron count rate, and other calculated results are consistent with the experimental results, verifying the accuracy of the boron physical model. This physical model can be used for more refined computational analysis or to optimize the current physical design of the boron meter, thus saving experimental costs.